The problem of the inauthenticity of knowledge in Latin America (Global Journal of Human-Social Science, 2024)
In Latin America the production of scientific knowledge in the human sciences in general and sociology in particular has been characterized by a double concern On the one hand the arrival of ideas concepts and theories from outside the continent continues to cause strangeness as to their relevance and suitability for a different social and economic context On the other hand as a way out of this nonconformity there has been a search for a common epistemological basis about ourselves that would underpin and clarify this singularity It is argued that an alternative to overcome this uncertainty lies in the Latin America s condition of dependence that is in the specific way in which we are inserted into the world capitalist system as a fundamental element in understanding or explaining recurring impasses and challenging novelties In fact it is about strengthening a fruitful tradition which has provided us with great insights into countless objects of study
Keywords: latin america – dependence – knowledge – sociology – inauthenticity